A Critical Analysis of Ogungbemi’s Ethics of Nature-Relatedness and Tangwa’s Ecobio-Communitarianism - Edor, Edor John; Ushie, Abel Idagu; Ogelenya, Grace (Studia Ecologiae et Bioethicae, 2025)
Global concerns about the environmental crisis have sparked diverse ethical responses, including normative environmental ethics, sentient ethics, biocentric ethics, ecocentric ethics, and ecofeminist ethics. While these approaches are deeply rooted in Western cultural perspectives, addressing global environmental challenges demands broader, cross-cultural insights. Given that African philosophers are now concerned with environmental issues and philosophising, it becomes necessary to contribute to this nascent field of African environmental philosophy. This paper contributes to the growing literature in African environmental philosophy by critically analysing the works of Segun Ogungbemi and Godfrey Tangwa. Ogungbemi advocates for an “ethics of nature-relatedness,” emphasizing the interdependence of humans and nature, while Tangwa proposes “ecobio-communitarianism,” which underscores the interconnectedness of all living beings and non-living entities within the ecosystem. The aim of this critical analysis is to deepen the discourse on African environmental ethics and highlight the potential contributions of ethics of nature-relatedness and ecobio-communitarianism to global environmental philosophy.